Techno-economic, environmental, and safety assessment of hydrogen powered community microgrids; case study in Canada. (18th May 2017) - Mukherjee, Ushnik; Maroufmashat, Azadeh; Ranisau, Jonathan; Barbouti, Mohammed; Trainor, Aaron; Juthani, Nidhi; El-Shayeb, Hadi; Fowler, Michael
Abstract: This paper proposes a comprehensive design of a renewable hydrogen powered microgrid that can provide backup power to a community in Cornwall, Ontario when disconnected from the power grid. The work employs the implementation of the energy hub concept to optimally design and operate energy generation systems to meet energy loads of a community. Solar PVs, wind turbines, electrolysers, hydrogen tanks, fuel cells and fuel cell vehicles are considered as the components that make up the entire system providing energy within the community. Failure mode and effect analysis (FMEA) is done to assess the safety of hydrogen based microgrid. The major load centers include a fresh food distribution center and a residential complex, where the peak demand is ∼5410 kW. The results of a mixed integer linear programming optimization problem show that a renewable energy generation system size of 2000 kW (400 kW-solar Photovoltaic and 1600 kW-wind turbine) is required. In addition to this, a backup fuel cell generation system of 3000 kW is also needed for the two-day blackout period. One of the positive attributes of implementing vehicle to grid services during islanded operation mode is that it enables the community to offset investment in fuel cell backup generation capacity by 1000 kW. Thirty-eight Toyota Mirai have been used to provide the vehicle to grid service. Due to the scale of the system, it is observed that even after proposing the use of existing market pricing mechanisms for the services offered by the microgrid, the energy system does not have a positive net present value at the end of its project life. Therefore, further economic incentives in the form of bundling costs need to be sanctioned for cleaner microgrid energy systems to be developed. This submission was the Grand Prize Winner of the Hydrogen Education Foundation's 2016 Hydrogen Student Design Contest. Highlights: Optimal design of renewable based hydrogen powered microgrid was done. The hydrogen based microgrid provides backup for 2 days in islanded operation mode. Hydrogen fuel cell vehicles provide vehicle to grid (V2G) service during islanded operation mode. A failure mode and effects analysis (FMEA) of hydrogen based microgrid was done. Premium pricing mechanisms suggested for services provided by microgrid energy system.